The Implementation of the Enriched Virtual Model in Lexical Studies Class at Universitas PGRI Semarang - Theresia Cicik Sophia Budiman; Januarius Mujiyanto; Sri Wuli Fitriati; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2021)
In the pandemic era as seen from the current condition, people are trapped with the situation because of the Covid-19 virus. This Covid-19 pandemic has influenced many sectors, one of them is in educational sector. Students and teachers should understand the use of technology media to assist them in the teaching and learning process. Based on that reason, this research aims to know the implementation of the Enriched Virtual model in Lexical Studies I class at Universitas PGRI Semarang as seen from the planning, the practice and the assessment of students ‘tests. This is qualitative research by collecting the data from the design of the lesson plan of Lexical Studies I course, the observation sheet, and the score of students’ pre-test and post-test. The findings show that the implementation of the Enriched Virtual model in Lexical Studies course is conducted through the design of Lexical Studies I lesson plan, the implementation itself, and the assessment of students’ tests. From the design of Lexical Studies I lesson plan, it becomes the guideline for the lecturer to assist her in teaching and learning process by using the Enriched Virtual model. The implementation of the Enriched Virtual model enhances students’ learning experience and offers insights on course delivery by using the Enriched Virtual model in order to achieve the learning objectives of Learning Studies I course. Then the assessment result is to prove that the implementation of the Enriched Virtual model can improve students’ result.